Assessment of rainfall and wind induced soil erosion at Cameron Highlands, Pahang, Malaysia - Wafa', Mohd Salleh (2012)
The increasing of population and due to urbanization have caused many of tropical countries decided to execute the agriculture activities at the highlands in order to fulfil the demand from the populace. However, agricultural activities on the steep lands have resulted in increasing of soil erosion and also leading to significant externalities such as sedimentation of waterways and reservoir, nutrient losses in runoff water, and decline in down-stream water quality (Midmore et al., 1996). Soil degradation by rainfall and wind-induced erosion is a serious problem and will remain so during the 21st century, especially in developing countries of tropics and subtropics. The aim of this research is to assess the rainfall and wind induced soil erosion at Cameron Highlands. After obtaining the wind speed and rainfall data, the monthly rainfall erosivity is calculated using the rainfall erosivity model introduced by Dumsday and Huang (1992). Based on this model, the result shows that the rainfall is a dominant to erosivity while wind speed does not has too much of impact on erosivity as the correlation of erosivity and wind speed is only 0.70%. More direct correlation should be developed in the future research in order to get the accurate result between wind speed and erosivity. A lot of parameters should be considered such as wind direction, soil surface roughness, wind energy and other parameters to get detail result on wind speed effecting on erosivity. It is also suggested to do a study on tillage effect on soil loss that might has bigger impact on erosivity compared to wind speed.